Dual bulk and interface engineering with ionic liquid for enhanced performance of ambient-processed inverted CsPbI3 perovskite solar cells. (1st July 2022) - Wang, Kun; Su, Zeyuan; Chen, Yali; Qi, Heng; Wang, Ting; Wang, Hao; Zhang, Youqian; Cao, Li; Ye, Qian; Huang, Fobao; Tong, Yu; Wang, Hongqiang
Highlights: Ionic liquid of BMIMPF6 is utilized for the first time as dual bulk and interface modifier for fabricating inorganic perovskite solar cells in ambient air. The proposed strategy enables effective protection of CsPbI3 perovskite structure and enhancement of charge carrier transport/extraction. Dramatically improved efficiency and stability of ambient-processed inverted CsPbI3 perovskite solar cells are achieved. Abstract: All-inorganic cesium lead iodide (CsPbI3 ) perovskites with superior thermal stability are attractive candidates for perovskite solar cells (PSCs). Fabricating such inorganic PSCs in the ambient atmosphere is desirable for practical production, however, the challenge remains in inhibiting the phase transition of CsPbI3 in ambient air. Herein, we demonstrate a dual bulk and interface engineering using ionic liquid to stabilize CsPbI3 perovskite structure, thus enhancing the performance of ambient-processed inverted CsPbI3 PSCs. Such dual bulk and interface engineering is found effective not only in suppressing the bulk and interfacial charge carrier recombination and enhancing charge carrier transport and extraction, but also in protecting CsPbI3 crystal structure by leaving hydrophobic alkyl chains coverage at the boundary and surface to prevent phase transition caused by moisture from ambient air. The optimized device fully processed in the open air with relative humidity up to 55% exhibits remarkably enhanced efficiency and stability over the control device, with the efficiency increasing from 8.6% to 13.21%, and 92% efficiency maintaining after storage for 1680 h, which outperforms the control device with only 82% retaining after 648 h storage. We thus believe this work can provide an efficient alternative for the low-cost fabrication of ambient-processible PSCs.